Distant Learning Satisfaction in High School Chemistry Amidst COVID-19 Pandemic: A Case Study - Maesaroh Maesaroh; Hari Sutrisno (Universitas Negeri Medan, 2024)
The aim of this research is to analyze the level of satisfaction with distance learning chemistry during the COVID-19 pandemic. This study used descriptive qualitative method. Data collection through a survey using google form to 449 respondents. The results of the analysis show that the COVID-19 pandemic has an impact on the level of student satisfaction, namely 18% very satisfied, 78% satisfied and 4% dissatisfied with distance learning chemistry. Students participate actively in taking chemistry lessons online. The distance learning system is not limited to being used during the COVID-19 pandemic, but can also be applied in normal conditions as modified learning with face-to-face learning.